Cardiorespiratory fitness attenuates the association between psychosocial stress and cardiometabolic risk – Results from the SCAPIS population - Frida Griffin; Jonatan Fridolfsson; Daniel Arvidsson; Ingibjörg H. Jonsdottir; Mats Börjesson (PLoS ONE, 2026)
Aims Low cardiorespiratory fitness (CRF) and high psychosocial stress can contribute to cardiovascular disease. CRF is a strong predictor of cardiovascular outcomes, yet population-based evidence on whether CRF buffers stress-related risk remains limited. This study aims to (1) examine associations between CRF, stress, and cardiometabolic risk; (2) assess whether CRF moderates the relationship between stress and cardiometabolic risk; and (3) explore whether associations between CRF and cardiometabolic risk are stronger among high-stress individuals. Methods We included 4,207 healthy, middle-aged participants from the Swedish CArdioPulmonary bioImage Study (SCAPIS), conducted 2013–2018. CRF was estimated using submaximal cycle testing (ml/min/kg). Perceived psychosocial stress was measured using a single self-reported item dichotomised into “low” and “high”. Ten cardiometabolic outcomes were assessed, including waist circumference, BMI, and blood pressure. Cross-sectional associations were analysed in R, using t-tests and multiple linear regression. Results Individuals reporting high stress had lower CRF (−1.7 ml/min/kg, p < .001) and less favourable cardiometabolic profiles. CRF moderated the relationship between stress and waist circumference, BMI, systolic- and diastolic blood pressure. For each 1 ml/min/kg higher CRF, the stress-related association was reduced by 0.17 cm in waist circumference (p < .001), 0.06 kg/m 2 in BMI (p < .001), 0.18 mmHg in systolic blood pressure (p = .030), and 0.13 mmHg in diastolic blood pressure (p = .020). Associations were 13–25% stronger in the high-stress group. Conclusion Higher CRF attenuated the association between psychosocial stress and cardiometabolic risk. Promoting physical activity to improve CRF could be important during periods of high stress to counteract stress-related cardiometabolic deterioration.